Prediction of Eating Problems in Children with Autism based on Resilience and Interactive Style of Mothers - Arash Shahriyari; Alireza Aghaz (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2020)
Aim and Background: Eating problems in children with autism spectrum disorders are more than their healthy counterparts and can negatively affect their health, communication and other disabilities. Maternal resilience and interactive style play a vital role in the health, behaviors and quality of life of these children. The aim of this study was to predict the eating problems of children with autism spectrum based on resilience and interactive style of their mothers. Methods and Materials: This is a descriptive and correlational study. The statistical population of this study was children with autism spectrum disorders aged 4 to 7 years who referred to private rehabilitation centers in Tehran. The sample size of 90 people was selected by available sampling method. Data were collected using the Child Eating Behavior Questionnaire, Resilience Scale, and Child-Parent Relationship Scale. The data of this study were analyzed using SPSS software and Spearman correlation method. Findings: Based on the findings, increasing maternal resilience reduced eating problems in children with autism spectrum disorders (p<0.01). In addition, increasing the quality of the parent-child relationship reduces eating problems in these children (p<0.05). Also, increasing the resilience of these mothers directly affects the quality of parent-child interaction (p<0.01). Maternal resilience can predict eating problems in children with autism spectrum disorder. Conclusions: Resilience and communication style of mothers play a key role in the development of nutritional problems in children with autism spectrum disorders. It seems that by strengthening the parent-child relationship and mothers' resilience, the eating problems of these children can be reduced.